Pengaruh Antioksidan Eksopolisakarida dari Tiga Galur Bakteri Asam Laktat pada Sel Darah Domba Terinduksi tert-Butil Hidroperoksida (t-BHP) - Afiati, Fifi; Widad, Nina Ainul; ., Kusmiati (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTExopolysaccharides (EPS) are water soluble polymers synthesized by three strains of lactic acid bacteria (LAB) namely EPS-S1, EPS-S2 and EPS-S7. Some exopolysaccharides (EPSs) produced by lactic acid bacteria (LAB) present potential health-beneficial properties, such as immune stimulation and antioxidative activities. Antioxidants function in several ways including preventing the formation of radicals, scavenging free radicals, formation of hydrogen peroxide and lipid peroxides. The Objectives of this research were to evaluate the antioxidant activities of exopolysaccharides (EPS) extracts from lactic acid bacteria (LAB). The extracts were investigated by using in vitro assays induced tersier-Butilhidroperoksida (t-BHP) 6 µg.ml-1 red blood cell (RBC) for their effects on lipid peroxidation malondealdehyde (MDA) level and activities of some antioxidant enzymes which includes catalase (CAT) and superoxide dismutase (SOD). Six groups consisted of 3 replicated per group; (I) normal control, RBC (II) negative control, RBC+ t-BHP (III) positive control, RBC+t-BHP+vitamin-C, and (IV-VI) samples, RBC+t-BHP+EPS (S1, S2 and S7) extracts. The results showed that exopolysaccharides (EPS) of three strains of lactic acid bacteria (LAB) increased catalase (CAT) and superoxide dismutase (SOD) enzyme activity and decreased malondealdehyde (MDA) content, exopolysaccharides (EPS)-S2 most potential to increase the activity of catalase (CAT; 77.46%) and superoxide dismutase (SOD; 33.87%) enzyme and inhibit the increase malondealdehyde (MDA; 32.19%) levels. Keywords: exopolysaccharide, lactic acid bacteria, malondealdehyde (MDA), superoxide dismutase (SOD), catalase (CAT)